Misplacement of a Port Catheter: A Differentiated View. (26th December 2017) - Evers, Christoph; Gazis, Angelos; Thuss-Patiance, Wendy; Kretzschmar, Albrecht
Abstract : Clinical radiological controls after the insertion of central venous catheters (CVC) are of high importance. Misplacement of the CVC, outside of large vessels, as described in our first case, occurs in more than 7% of cases and may be associated with life-threatening events. A persistent left-sided superior vena cava (PLSSVC) occurs in 0.3–0.5% of the standard population. In one of the cases a CT scan of the chest showed the catheter in a PLSSVC. Neoadjuvant radiochemotherapy was indicated in a patient with an adenocarcinoma of the oesophagus. Under hospitalised monitoring, full-dose chemotherapy was given. Consequences for the patients arise when the findings are known for future interventions. If a PLSSVC is expected and a CVC is to be inserted, the venous return to the heart should be evaluated first, to preclude a possible backflow to the left atrium. With this constellation, a right-to-left shunt can be expected in in 10% of cases. Affected patients face a high risk of developing cardioembolic events.